2021
DOI: 10.3390/molecules26237278
|View full text |Cite
|
Sign up to set email alerts
|

Widely Targeted Metabolomics Analysis Reveals Great Changes in Nonvolatile Metabolites of Oolong Teas during Long-Term Storage

Abstract: As a semifermented tea, oolong is exceedingly popular worldwide for its elegant, flowery aroma and mellow, rich taste. However, recent marketing trends for old oolong teas and their chemical quality largely remain unexplored. In this study, we applied widely targeted metabolomics using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) combined with multivariate analysis to investigate the chemical change of oolong teas in the aging process. With the increasing of store time, most no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Polysaccharides and flavonoids have been shown to alleviate colitis by inhibiting the expression of inflammatory factors and modulating the gut microbiota (F. Huang et al, 2016 ). For AOT stored for 20 to 30 years, the comparison revealed that the complex and diverse water-soluble polysaccharides and flavonoids in AOT tended to increase year by year as the storage time increased, which is consistent with the study of Hong ( Hong et al, 2021 ) et al . and Peng ( Peng et al, 2022 ) et al .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Polysaccharides and flavonoids have been shown to alleviate colitis by inhibiting the expression of inflammatory factors and modulating the gut microbiota (F. Huang et al, 2016 ). For AOT stored for 20 to 30 years, the comparison revealed that the complex and diverse water-soluble polysaccharides and flavonoids in AOT tended to increase year by year as the storage time increased, which is consistent with the study of Hong ( Hong et al, 2021 ) et al . and Peng ( Peng et al, 2022 ) et al .…”
Section: Discussionsupporting
confidence: 90%
“…Further comprehensive analysis of the results of inflammatory factors, tight junction proteins, oxidative stress factors and gut microbiota showed that AOT from different storage periods provided different degrees of relief in DSS-induced colitis mice. This is an intriguing finding, as the phytochemical makeup of AOT varies according to storage duration ( Hong et al, 2021 , Peng et al, 2022 ). The phytoactive components of AOT were analyzed at four different storage periods.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The content of catechins in oolong tea gradually decreases with an increase in the degree of roasting [11]. During long-term storage of oolong tea, the content of non-gallated catechins gradually decreases, while the content of gallated catechins remains relatively stable [12].…”
Section: Introductionmentioning
confidence: 98%
“…Generally, the formation of the characteristic flavor is a consequence of multiple stresses in the postharvest manufacturing of oolong tea ( 6 ). While many studies have been centered on using different tea varieties to understand and investigate the characteristic flavor and formation mechanism in each manufacturing process of oolong tea, such as Tieguanyin after roasting ( 7 ), Shuixian tea after long-term storage ( 8 ), Wuyi rock tea produced with four tea cultivars (including Rougui, Dahongpao, Qizhong and Shuixian) at three roasting levels (low, moderate and sufficient) ( 9 ) and oolong tea processed with Chin-Hsin-Dah-Pang and Chin-Hsin-Gan-Tzu two cultivars at the turning-over stage ( 10 ). Meanwhile, nonvolatile compounds linked to tea taste have been categorized according to five tasting properties, namely, bitterness, astringency, umami, sweetness, and sourness ( 11 ), and the characteristic flavor of oolong tea has an important correlation with both their contents and types.…”
Section: Introductionmentioning
confidence: 99%